Using simulated annealing algorithm for optimization of quay cranes and automated guided vehicles scheduling - Homayouni, Seyed Mahdi; Tang, Sai Hong; Ismail, Napsiah; Mohd Ariffin, Mohd Khairol Anuar (Academic Journals, 2011)
Sea port container terminals play an important role in the national and regional economy. The integrated scheduling of handling equipment has been recently investigated in literature to improve the performance of the container terminals. In this paper, an integrated scheduling of quay cranes and automated guided vehicles is formulated as a mixed integer linear programming model. This model minimizes the makespan of all the loading and unloading tasks for a set of cranes in a scheduling problem. Based on the simulated annealing (SA) algorithm, a scheduling method is proposed to solve the problem in a relatively short period of time. Comparison of the respective results of the mathematical model and the SA algorithm evidently shows acceptable performance of the proposed SA algorithm in finding good solutions for practical scheduling problems. Moreover, the effects of three cooling processes and two sets of control parameters on the best solution of the SA are investigated.